(untitled) (Herald of Journalism, 2016)
The author of article considers theoretical and practical questions of use by journalists in publicistic texts of an artistic touch known in the theory of journalism as convention. On the example of publicistic essays of prominent Kazakhstan publicists of Gerold Belger, Sagymbay Kozybayev, etc. examples of publicistic convention are given. he problem is considered in a debatable foreshortening and from the point of view of its further perspective development from a position of continuous updating.